If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = 4y + -2 Reorder the terms: -10 = -2 + 4y Solving -10 = -2 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -10 + -4y = -2 + 4y + -4y Combine like terms: 4y + -4y = 0 -10 + -4y = -2 + 0 -10 + -4y = -2 Add '10' to each side of the equation. -10 + 10 + -4y = -2 + 10 Combine like terms: -10 + 10 = 0 0 + -4y = -2 + 10 -4y = -2 + 10 Combine like terms: -2 + 10 = 8 -4y = 8 Divide each side by '-4'. y = -2 Simplifying y = -2
| 8x+6=4x+54 | | 28=-3f+4 | | 4(5x+7)=-17+5 | | 2g+1=17 | | m^2+9x=-18 | | 3x-2=12+3x | | 5n-8=-28 | | 3(x-2)+2(x+-1)=12 | | 5=2f+5 | | 36=6s+6 | | -11-(-12)=x/5 | | 7k-21=4k+9 | | 0.4x+0.8x-4=2 | | 28=3f+7 | | 5t-2(5+4t)=t-6 | | 2y-1=-13 | | -39=5v-9 | | -22=3x+5 | | 16-6n=4n-4 | | -3u+7=1 | | 37+4y-8=17y-11-5y | | x+17+2x=-2-2x-6 | | 1/4(20+x)=25 | | 2u-1=17 | | 4(5y-7)-21y=-14 | | -14=2h+4 | | 2.7y=12.42 | | 5t+1=-29 | | 2x+32=x+28 | | -12=3h | | 21p+4p^2=-20 | | 9d+11-15d-1=-42 |